Perancangan dan Analisis Mesin Pencacah Rumput Untuk Peningkatan Efisiensi Pakan Ternak di Desa Cipicung - Nota, Nota Ali Sukarno; Aziz, Abdul; Gunawan, Leo Van; Nabilah, Prita Retno; Riandi, Maxc Reno Rona (Politeknik Negeri Indramayu, 2025)
The process of chopping grass for animal feed in Cipicung Village, Sumedang Regency, West Java Province still uses manual methods using simple tools such as machetes and sickles. The use of this tool takes a long time, slowing down the feeding process and requiring human labor. Therefore, the manufacture of a grass chopping machine is needed to simplify the chopping process, make time more efficient and to minimize accidents during the chopping process. The design methods used to obtain data include; field surveys, drawing planning, calculations to determine the components to be used. Based on the calculation results, the machine can chop grass as much as 900 kg/hour or 15 kg/minute. For the rotation of the grass chopper blade needed to chop in 1 minute is 937.5 rpm. While the calculation results of the maximum rotation on the axle pulley are 1800 rpm, then the design can be said to be successful because the rotation of the axle pulley has exceeded the rotation of the chopper blade, which is 937.5 rpm. The simulation results obtained a von misses value of 29.664 N/mm² and a maximum displacement of 0.084 mm and a factor of safety on the frame with a maximum value of 1.5.